Recommendations from the Canadian Association of Head and Neck Surgical Oncology for the Management of Head and Neck Cancers during the COVID-19 pandemic - Daniel A. O’Connell; Hadi Seikaly; Andre Isaac; Justin Pyne; Robert D. Hart; David Goldstein; John Yoo; Canadian Association of Head and Neck Surgical Oncology (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Introduction The SARS-CoV-2 virus (COVID19) pandemic has placed extreme pressures on the Canadian Healthcare system. Many health care regions in Canada have cancelled or limited surgical and non-surgical interventions on patients to preserve healthcare resources for a predicted increase in COVID19 related hospital admissions. Also reduced health interventions may limit the risk of possible transmission of COVID19 to other patients and health care workers during this pandemic. The majority of institutions in Canada have developed their own operational mandates regarding access to surgical resources for patients suffering from Head and Neck Cancers during this pandemic. There is a large degree of individual practitioner judgement in deciding access to care as well as resource allocation during these challenging times. The Canadian Association of Head and Neck Surgical Oncology (CAHNSO) convened a task force to develop a set of guidelines based on the best current available evidence to help Head and Neck Surgical Oncologists and all practitioners involved in the care of these patients to help guide individual practice decisions. Main body The majority of head and neck surgical oncology from initial diagnosis and work up to surgical treatment and then follow-up involves aerosol generating medical procedures (AGMPs) which inherently put head and neck surgeons and practitioners at high risk for transmission of COVID19. The aggressive nature of the majority of head and neck cancer negates the ability for deferring surgical treatment for a prolonged period of time. The included guidelines provide recommendations for resource allocation for patients, use of personal protective equipment for practitioners as well as recommendations for modification of practice during the current pandemic. Conclusion 1. Enhanced triaging should be used to identify patients with aggressive malignancies. These patients should be prioritized to reduce risk of significant disease progression in the reduced resource environment of COVID19 era. 2. Enhanced triaging including aggressive pre-treatment COVID19 testing should be used to identify patients with high risk of COVID19 transmission. 3. Enhanced personal protective equipment (PPE) including N95 masks and full eye protection should be used for any AGMPs performed even in asymptomatic patients. 4. Enhanced PPE including full eye protection, N95 masks and/or powered air purifying respirators (PAPRs) should be used for any AGMPs in symptomatic or presumptive positive COVID 19 patients.